State of research on public service management: Identifying scientific gaps from a bibliometric study - Juliani, Fernando [UNESP]; Oliveira, Otavio Jose de [UNESP] (Elsevier B.V., 2016)
Academic interest in aspects of the public sector has grown considerably, especially in the areas of social sciences, management and finance. In the studies that are specifically designed to public service management, this growth was herein observed and analyzed. The current paper presents and analyses major publications involving public service management in the decade of 2004-2014, so as to identify scientific gaps to promote and guide new studies on the aforementioned subject. For this purpose, a bibliometric study of related scientific papers was carried out. The data was collected from the Scopus and Web of Science databases, enabling an analysis of the most cited articles, keywords and authors, and of the most recently published article on public service management by each of these cited authors. Based on this analysis, it was observed that the New Public Management model is the principal object of research on public service management, and that the scientific gaps mainly involve the public service motivation. In this way, the main scientific contribution of the present paper is to assist new studies on public service management, including the expansion of existing theory and innovative model proposals. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Public service management; Bibliometric study; State of research; Scientific gap